Strategies for responsible innovation : perspectives, projects, and tools for co-creating the future we want - Martinuzzi, André, 1964-; Findler, Florian; Graf, Alexander (Editor) (Routledge, 2024)
"How can responsible business work in the highly competitive areas of innovation? Focusing on business opportunities and illustrating how Responsible Innovation can be successfully implemented in practice, this book captures experiences and insights from key decision-makers in business, politics and academia, to answer this question. In addition to interviews with leading thinkers in the field, the book describes the experiences of 8 EU projects and provides tools for responsible innovation in the business sector. The examples in this book illustrate how to move from a vague societal aspiration to a business case for responsible innovation, and provide a compelling argument for collaboration at the important intersection between government, business and academia. In this way, responsible innovation transcends a singular market-based approach to deliver value at many levels, co-creating in a truly inclusive manner. The book sheds light on the strategic benefits of applying the concept of responsible innovation in practice and offers concrete tools for its implementation. Aimed primarily at managers of innovation processes in organisations, and consultants and facilitators working on responsible innovation and sustainability management, the book also provides insight into the logic and principles of responsible innovation management for academics, policy-makers, and civil society organizations, helping them better communicate their requirements to business"-- Provided by publisher.
Keywords: Organizational change -- Moral and ethical aspects.; Sustainable development.; elektronické knihy; electronic books